INOVASI MIXED REALITY SEBAGAI MEDIA PEMBELAJARAN DAN PENGENALAN KAMPUS UNDIPA MAKASSAR BERBASIS VIRTUAL - Saenong, Andi; Rahman, Muhammad Rusdi (Jurnal Media Informatika, 2024)
The innovation of Mixed Reality (MR) technology, which combines elements of Virtual Reality (VR) and Augmented Reality (AR), provides an interactive learning experience. This research aims to develop an MR-based application at Universitas Dipa Makassar (UNDIPA) to support digital learning and campus promotion. Utilizing Oculus Quest devices and software such as SketchUp, Photoshop, and SimLab, this study produced realistic virtual spaces that allow students to explore campus buildings, classrooms, and facilities interactively. The application was tested using the System Usability Scale (SUS), achieving an average score of 72.5, indicating a "Good" category. The implementation of MR is expected not only to enhance learning effectiveness but also to strengthen the university’s branding as a modern and technology-adaptive institution. The MR-based innovation enables a unique and flexible campus exploration experience that is unrestricted by time or place, equipping students with essential digital skills for the future.